Topical Rapamycin Therapy to Alleviate the Cutaneous Manifestations of Tuberous Sclerosis Complex: A Double-Blind, Randomized, Controlled Trial to Evaluate the Safety and Efficacy of Topically Applied Rapamycin - Koenig, Mary Kay (Springer International Publishing, 2012)
BACKGROUND AND OBJECTIVES: Facial angiofibromas are disfiguring facial lesions, present in up to 80% of patients with tuberous sclerosis complex. Recent elucidation of the complex cell signaling pathways that are disrupted in tuberous sclerosis indicates that rapamycin may be successful in alleviating the appearance of these lesions. The objectives of the current study were to evaluate the safety of topically applied rapamycin in patients with tuberous sclerosis complex and to determine its potential effectiveness in treatment of facial angiofibromas. PATIENTS AND METHODS: The study was a prospective, randomized, double-blind, placebo-controlled study performed at the University of Texas Health Science Center at Houston. Study subjects were recruited from the patient populations at the University of Texas Tuberous Sclerosis Center of Excellence. All subjects were over the age of 13 years and had a diagnosis of tuberous sclerosis complex. Subjects were excluded if they were using any form of rapamycin or if they were pregnant. Study subjects applied the study product to their facial angiofibromas nightly for a duration of 6 months. The investigational product contained one of three doses of rapamycin compounded with Skincerity®: (i) no rapamycin; (ii) 1 mg of rapamycin per 30 cc (0.003%); or (iii) 5 mg of rapamycin per 30 cc (0.015%). Plasma rapamycin concentrations were measured monthly to test for systemic absorption. Complete blood counts were performed monthly to test for anemia, neutropenia, or thrombocytopenia. Upon completion of the trial, subjects were asked if the formulation had improved the appearance of their facial angiofibromas. RESULTS: Twenty-three subjects completed the study. There was no detectable systemic absorption of rapamycin (all blood concentrations were <1.0 ng/mL). There were no significant changes in white blood cell, red blood cell, or platelet counts. Seventy-three percent of subjects in the treatment arms versus 38% of subjects in the placebo arm reported a subjective improvement in the appearance of their facial angiofibromas. CONCLUSION: The application of low-dose topical rapamycin (0.003–0.015%) to the face can safely decrease the appearance of facial angiofibromas in patients with tuberous sclerosis complex. TRIAL REGISTRATION: ClinicalTrials.gov Identifier: NCT01031901